Hepcidin Plays a Key Role in 6-OHDA Induced Iron Overload and Apoptotic Cell Death in a Cell Culture Model of Parkinson’s Disease - Qi Xu; Anumantha G. Kanthasamy; Huajun Jin; Manju B. Reddy (Parkinson's Disease)
Background. Elevated brain iron levels have been implicated in the pathogenesis of Parkinson’s disease (PD). However, the precise mechanism underlying abnormal iron accumulation in PD is not clear. Hepcidin, a hormone primarily produced by hepatocytes, acts as a key regulator in both systemic and cellular iron homeostasis. Objective. We investigated the role of hepcidin in 6-hydroxydopamine (6-OHDA) induced apoptosis in a cell culture model of PD. Methods. We downregulated hepcidin using siRNA interference in N27 dopaminergic neuronal cells and made a comparison with control siRNA transfected cells to investigate the role of hepcidin in 6-OHDA induced neurodegeneration. Results. Hepcidin knockdown (32.3%, P<0.0001) upregulated ferroportin 1 expression and significantly (P<0.05) decreased intracellular iron by 25%. Hepcidin knockdown also reduced 6-OHDA induced caspase-3 activity by 42% (P<0.05) and DNA fragmentation by 29% (P=0.086) and increased cell viability by 22% (P<0.05). In addition, hepcidin knockdown significantly attenuated 6-OHDA induced protein carbonyls by 52% (P<0.05) and intracellular iron by 28% (P<0.01), indicating the role of hepcidin in oxidative stress. Conclusions. Our results demonstrate that hepcidin knockdown protected N27 cells from 6-OHDA induced apoptosis and that hepcidin plays a major role in reducing cellular iron burden and oxidative damage by possibly regulating cellular iron export mediated by ferroportin 1.